Chance or Ability? The Efficiency of the Football Betting Market Revisited - Luca Rebeggiani; Johannes Gross (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
The extent of market efficiency induced by rational behaviour of market participants is central for economic research. Many economists have already examined sports-betting markets as a laboratory to better understand trading behaviour and efficiency of stock prices while avoiding to jointly test the hypothesis of a correct capital market model. The following paper will investigate whether the European football betting market fulfils the efficiency paradigm introduced by Fama (1970) with a unique dataset allowing for an investigation of the German betting market in view of its regulatory changes recently. The analysis contributes to the literature by conducting a variety of empirical strategy including rational expectation frameworks and an ordered choice model to stress the ex post market performance from a weak and semi-strong form perspective. In view of existing market distortions as taxes, switching costs of changing betting providers and limitation in competition, the results of the analysis are indicative of a rational market equilibrium surprisingly close to the efficiency benchmark.1
Keywords: G14; L83; Z2; 330; Gambling; Sports Betting; Market Efficiency